Decreased Hepatocyte Growth Factor (HGF) and Gamma Aminobutyric Acid (GABA) in Individuals with Obsessive-Compulsive Disorder (OCD) - Anthony J. Russo; Stefanie C. Pietsch (Biomarker Insights, 2013)
Introduction There is support for the role of gamma aminobutyric acid (GABA) in the etiology of mood disorders. Recent research has shown that hepatocyte growth factor (HGF) modulates GABAergic inhibition and seizure susceptibility. This study was designed to determine and correlate plasma levels of HGF and GABA as well as symptom severity in individuals with obsessive-compulsive disorder (OCD). Subjects and Methods Plasma from 15 individuals with OCD (9 males, 6 females;, mean age 38.7 years) and 17 neurotypical controls (10 males, 7 females; mean age 35.2 years) was assessed for HGF, GABA, urokinase plasminogen activator (uPA), and urokinase plasminogen activator receptor (uPAR) concentration using enzyme-linked immunosorbest assays ELISAs. Symptom severity was assessed in these OCD individuals and compared with HGF and GABA concentrations. Results In this preliminary study, individuals with OCD had significantly decreased HGF levels, decreased plasma levels of GABA and decreased uPA. We found that both uPA and uPAR levels correlate with HGF. Both low uPA and low uPAR levels correlate with high symptom severity in individuals with OCD. Low GABA levels in OCD individuals also correlate with high symptom severity. Discussion These results demonstrate a preliminary association between HGF, GABA, uPA levels, and OCD and suggest that plasma GABA and uPA levels are related to symptom severity in individuals with OCD.